Epistemologia do sensível na cultura contemporânea: estruturas de sentimento na compreensão da interface jornalismo/entretenimento - Coiro Moraes, Ana Luiza (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This paper aims to articulate the cultural hypothesis of "structures of feeling", proposed by Williams, together with the "method of comprehension" (Künsch) and what Muniz Sodré has named "strategies of the sensitive". In order to articulate such concepts, this article analizes two periods of technological expansion that had great impact on journalism (the Industrial Revolution and the contemporary microelectronics revolution) and then reaches the conclusion that structures of felling with an entertainment appeal are equally present in both periods. Palabras clave: Comunicación, la comprensión como método, estrategias de lo sensible, cultura, periodismo, ocio.